Chariot champions! - Strong, Jeremy (London Puffin, 2017)
Crazy capers abound in Ancient Rome! Croakbag the amazing talking raven tells the hilarious story of Perilus, the boy charioteer, his unpredictable family and Tiddles, the widdling elephant who's befriended them all. Another irresistible story for fans of David Walliams or David Baddiel, from Jeremy Strong, the original King of Comedy for young readers.
3-5
Keywords: Language